Challenges, Prospects, and Emerging Applications of Inkjet‐Printed Electronics: A Chemist's Point of View. (31st March 2022) - Lemarchand, Justin; Bridonneau, Nathalie; Battaglini, Nicolas; Carn, Florent; Mattana, Giorgio; Piro, Benoit; Zrig, Samia; Noël, Vincent
Abstract: Driven by the development of new functional inks, inkjet‐printed electronics has achieved several milestones upon moving from the integration of simple electronic elements (e.g., temperature and pressure sensors, RFID antennas, etc.) to high‐tech applications (e.g. in optoelectronics, energy storage and harvesting, medical diagnosis). Currently, inkjet printing techniques are limited by spatial resolution higher than several micrometers, which sets a redhibitorythreshold for miniaturization and for many applications that require the controlled organization of constituents at the nanometer scale. In this Review, we present the physico‐chemical concepts and the equipment constraints underpinning the resolution limit of inkjet printing and describe the contributions from molecular, supramolecular, and nanomaterials‐based approaches for their circumvention. Based on these considerations, we propose future trajectories for improving inkjet‐printing resolution that will be driven and supported by breakthroughs coming from chemistry. Abstract : We focus on the field at the junction of inkjet printing and high‐tech applications in optoelectronics, energy production and storage, and (bio)detection. We assess the micro‐ and nanostructuring inkjet printing methods and answer the following questions: What are the current strategies to improve the resolution of printed patterns? To what extent can advances in nanochemistry, supramolecular chemistry, and surface chemistry be integrated into printing strategies?